Sec35p, a Novel Peripheral Membrane Protein, Is Required for ER to Golgi Vesicle Docking - VanRheenen, Susan M. (The Rockefeller University Press, 1998)
SEC35 was identified in a novel screen for temperature-sensitive mutants in the secretory pathway of the yeast Saccharomyces cerevisiae (Wuestehube et al., 1996. Genetics. 142:393–406). At the restrictive temperature, the sec35-1 strain exhibits a transport block between the ER and the Golgi apparatus and accumulates numerous vesicles. SEC35 encodes a novel cytosolic protein of 32 kD, peripherally associated with membranes. The temperature-sensitive phenotype of sec35-1 is efficiently suppressed by YPT1, which encodes the rab-like GTPase required early in the secretory pathway, or by SLY1-20, which encodes a dominant form of the ER to Golgi target -SNARE–associated protein Sly1p. Weaker suppression is evident upon overexpression of genes encoding the vesicle-SNAREs SEC22, BET1, or YKT6. The cold-sensitive lethality that results from deleting SEC35 is suppressed by YPT1 or SLY1-20. These genetic relationships suggest that Sec35p acts upstream of, or in conjunction with, Ypt1p and Sly1p as was previously found for Uso1p. Using a cell-free assay that measures distinct steps in vesicle transport from the ER to the Golgi, we find Sec35p is required for a vesicle docking stage catalyzed by Uso1p. These genetic and biochemical results suggest Sec35p acts with Uso1p to dock ER-derived vesicles to the Golgi complex.